8 Therapy resistance in HNSCC – Enhanced levels of the cytoprotective protein survivin is mediated by down-regulation of microRNA-542-3p. Issue 5 (May 2015) - Gößwein, D.; Bäcker, S.; Schlesiger, S.; Epple, M.; Wünsch, D.; Wollenberg, B.; Stauber, R.; Knauer, S.
Abstract : Introduction: Head and neck squamous cell carcinomas (HNSCC) are characterized by overexpression of anti-apoptotic proteins (IAP). Survivin's dual role as an apoptosis inhibitor and a mitotic effector positioned this smallest member of the IAP family in the front line of cancer research. Survivin plays an essential role in mediating resistance to chemo- and radiation-therapy and thus, has direct clinical relevance. Methods and results: MicroRNAs (miRNAs) are deregulated in a variety of human cancers, including HNSCC. Among several miRNAs, miR-542-3p was found to be down-regulated in HNSCC tumors from patients and established HNSCC tumor cell lines. When analyzing the pathobiological relevance of miR-542 in HNSCC tumor biology, we found that miR-542-3p over-expression reduced cell viability and improved chemotherapy-induced apoptosis in HNSCC tumor cell lines. Upon miR-542-3p over-expression, we observed a dose-dependent down-regulation of Survivin levels, which could be rescued by enforced ectopic Survivin expression but not by a Survivin mutant currently isolated from primary tumor cells. Bioinformatic prediction as well as reporter assays confirmed direct targeting of Survivin by miR-542-3p. Targeting Survivin by siRNA or with miR-542-3p-loaded nanoparticles synergistically sensitized HNSCC tumor cells to irradiation- or chemotherapeutic-induced cell death. Conclusion: Collectively, miR-542-3p seems to exerts its tumor suppressive function in HNSCC by targeting Survivin. Exploiting miR-542-3p re-expression by chemical or genetic decoys could be a promising therapeutic strategy for treating HNSCC.